Method Approaches to Prevent Leakage Cell Stack of Vanadium Redox Flow Battery (VRFB) - Suhailah, Sujali; Mohd Rusllim, Mohamed; Siti Adiha, Md. Don; Nadhirah, Yusoff (2016)
This paper present the method to solve the leakage problem for a unit cell Vanadium redox flow battery (VRFB) in detecting the several main component involved and depict the weakness matter that causes leakage in order to improve the cell performance of VRFB. The 110.25cm2 unit cell stack of VRFB is carried out and setup with different size of rubber seal, membrane, type of fitting and layer of carbon felt use to elucidate the leakage problem. Result demonstrated that the usage of 3.0mm rubber seal, 12cm × 12cm Nafion 117 membrane, polypropylene type fitting and double layer of carbon felt showed positive feedback on solving the vanadium leakage. Suggestion for development and material improvements is highlighted.